Community Structure of Avifauna in The Rehabilitation Zone at Wonoasri Resort, Meru Betiri National Park - Arif Mohammad Siddiq; Hari Sulistiyowati; Munaa Aqidatul Ulaa; Fuad Bahrul Ulum; Firda Fadri (Jurnal Biodjati, 2024)
The rehabilitation zone of Meru Betiri National Park (MBNP) needs to be measured in relation to the success of ecosystem restoration. It can be used as a bioindicator, such as the bird community structure, hence their sensitivity to environmental changes. Therefore, the aims of this study are to determine the community structure of avifauna in the rehabilitation zone at Wonoasri Resort, MBNP including bird diversity, richness, dominance, feeding guilds, and their correlation with forest cover. The research was conducted in January 2023 in the Bonangan Block at three observation points, namely low vegetation cover, medium vegetation cover, and high vegetation cover. The ecological data, such as species and abundance, were collected using the point count method, while additional information related to conservation statuses were collected by web browsing on the IUCN Red List, the CITES appendix, and Indonesian government regulation (LHK No.106/2018). Data analysis used the dominance index, species diversity index (Shannon Wiener), and evaluated for statistical data using a Kruskal-Wallis (KW) test in R version 3.2.1. We recorded 38 bird species belonging to 31 genera and 21 families during this study. Among the feeding guilds, the insectivorous birds (14 species) were recorded as the higher species richness, followed by omnivorous (eight species), frugivorous (five species), granivorous (five species), carnivorous (four species), and nectarivorous (two species). The Kruskal-Wallis test shows there is a significant correlation among the feeding guilds (value of 11.644, with p-value = 0.040). Furthermore, referring to species richness, high vegetation cover areas have the highest species richness (30 species) compared to medium vegetation cover areas (27 species) and low vegetation cover areas (26 species). The dominance of avifauna species at this location falls into the low category (C = 0.07). According to the diversity index, avifauna in Bonangan Block is classified as a high category (H'=3.01).